Method of Proof of Work consensus algorithms comparison - Osadchuk, M.; Oliynykov, R. (Radiotekhnika, 2019)
A consensus algorithm is the most important part of any blockchain system. There are available various consensus algorithms that developers can utilize in their solutions, and such a decision making cannot be fully formalized due uncertainty in requirements and application environment. We propose a method that allows selecting of an optimal Proof of Work (PoW) consensus algorithm for newly developed blockchain system based on Analytic Hierarchy Process. Application of this method to various PoW algorithms with involvement of independent experts allowed to select dPoW as the best solution for the given conditions.